A Novel Adipokine, Asprosin May Play a Key Function in Metabolism - Ozbeg, Gulendam; Oz, Zeynep Dila; Ozdede, Mehmet Ridvan; Ozgen, Aslisah; Kocoglu, Samet Ramazan; Yasar, Abdullah; Kelestimur, Haluk (Wiley, 2023)
[Abstract Not Available]
Keywords: Asprosin; Metabolic Hormones; Glucagon; Corticosterone; Ghrelin; Growth Hormone